Metodologias ativas na formação de professores no ensino remoto: um relato de experiência sobre o tema resíduos sólidos - SILVA, Anna Caroline Bastos Dantas e (2024)
The purpose of this work is to provide teachers in initial training with the knowledge of different active methodologies to offer better scientific literacy through remote teaching. For this, it is essential to provide contact through experiences, with other practices that may arouse interest for both students and teachers. In this work, the question was: what are the challenges and contributions of a mini-course on solid waste for the initial training of teachers in the first years of elementary school? How can active methodologies, more specifically remote teaching, contribute to scientific literacy in the early years of teaching? For this, a short course was held, developed remotely, with synchronous and asynchronous activities. For data preparation and analysis, we have the following records: photography, audio-recording, video, notes and a questionnaire. The data are organized in the fourth chapter into sections called mandatory stops. In the data analysis, it was noticed that the participants engaged in the activities and reflected on their training, through texts written by the students themselves on the subject discussed, the photographic exhibitions and, in addition to contributing to the questionnaire, we were able to obtain responses from the interesting participants about the design of solid waste and the importance of this mini-course in teacher training. The present work sought to contribute to the formation of undergraduate students, more specifically from the Integrated Licensing course, by suggesting and analyzing a methodological action that aims to encourage scientific literacy through an active methodology during the period of emergency remote teaching.